Environmental Impact Assessment of Construction Activity on Air Quality - Goyal, Nitti (My University, 2018)
In order to study whether its beneficial or harmful effect, evaluation of any project through EIA has become must. Indian construction industry is rapidly growing at a rate of 9.2% whereas in world it is at an average of 5.5%. Undertaking EIA for construction industry can improve site management and can reduce environmental impacts both on and off site. In order to appreciate the risks posed by construction activities and taking steps to reduce incidents can help reduce costs and other effects. The report includes the various steps involved in EIA, environmental effects of construction industry and EIA with relation to construction industry. It further includes the air quality index (AQI) and cumulative ground level concentration of project site using Aermod as dispersion modeling software.
Keywords: EIA; Construction; Air Quality Index; AERMOD; Ground level concentration; Environmental Clearance